KEKHASAN DIKSI VALENTINO SIMANJUNTAK PADA PIALA PRESIDEN 2017 - Fatoni, Nur Rochman (Adabiyyāt: Jurnal Bahasa dan Sastra, 2017)
This research aims to explain the meaning and style of the unique dictions of langauge by Valentino Simanjuntak (VS) in the 2017 Presidential Cup and to explain the context of the underlying discourse. The research data is the unique diction list that VS often said in commenting on the match. The researcher uses the techniques of listening, noting, recording, transcripting, and documenting. In analyzing the data, researchers uses descriptive method. The results shows that the emergence of the unique dictions of VS is based on 3 contexts; namely physical, social, and epistemic context. The meaning analysis finds that VS uses the dictions to comment about what is happening in the pitch. He describes the events in the soccer matches by associating events in the pitch with events from various domains. The referred domains are household, romance, law, transportation. From the 24 data findings, the researcher finds 16 nouns dictions, 5 verbal dictions, a numeral diction, a minor phrases, and a sound imitations. VS’s dictions also have 2 pictoral meanings, 16 figurative meanings, 3 referential meanings, and 3 connotative meanings. VS uses 15 styles of metaphor and 5 styles of personification. There are 4 dictions that do not use any style.